Haloboration: scope, mechanism and utility. (15th July 2020) - Kirschner, Sven; Yuan, Kang; Ingleson, Michael J.
Abstract : Haloboration is a mostly overlooked technique, yet it is a powerful way of transforming alkynes stereoselectively into difunctionalised ambiphilic alkenes, which readily undergo a plethora of highly useful subsequent reactions. Abstract : Haloboration, the addition of B–X (X = Cl, Br, I) across an unsaturated moiety e.g., CY or CY (Y = C, N, etc. ), is dramatically less utilised than the ubiquitous hydroboration reaction. However, haloboration of alkynes in particular is a useful tool to access ambiphilic 1, 2-disubstituted alkenes. The stereochemical outcome of the reaction is easily controlled and the resulting products have proven to be valuable building blocks in organic synthesis and materials chemistry. This review aims at providing the reader with a brief summary of the historic development and of the current mechanistic understanding of this transformation. Recent developments are discussed and select examples demonstrating the use of haloboration products are given with a focus on the major areas, specifically, natural product synthesis and the development of boron-doped polycyclic aromatic hydrocarbons (B-PAHs).